SCOLIOSIS ASSESSMENT VIA TELEHEALTH USING PHOTOGRAMMETRY: DEVELOPMENT AND ACCURACY - ISIS JULIENE RODRIGUES LEITE NAVARRO; ERIC PARENT; JEFFERSON FAGUNDES LOSS; CLÁUDIA TARRAGÔ CANDOTTI (Coluna/Columna)
ABSTRACT The aim of this study was to present the development and assessment of the measurement accuracy of variables obtained with the Digital Imaged-based Postural Assessment (DIPA©) Capture app and Analysis software as part of a telehealth assessment protocol for idiopathic scoliosis. To enable the correct capture of photographic images for further analysis, the development of an application, called DIPA© Capture, was performed. A photo is automatically obtained only when the smartphone is aligned. The sample of this prospective study was composed of consecutive images of a real plumb line (RPL) taken by using the DIPA© Capture app. Once the photo was captured the app automatically drew a virtual plumb line (VPL). The inclination of the RPL and VPL was measured using the DIPA-S© eHealth Analysis software. A total of 50 images using the App comprised this sample. The median (min-max) inclination angle of the real and virtual plumb lines was 89.8° (88.6°-90°) with a 1.4° range and 90° (89.4°-90°) with a 0.6° range, respectively. The mean difference between the inclination of the two plumb lines (RPL - VPL) was very small -0.1°±0.04° (p= 0.017). The RMS error was 0.3°. The DIPA© Capture app and Analysis software for image acquisition and measurement was developed and is ready for testing with patients. The app accurately captures the alignment of the smartphone during the image acquisition and the software shows adequate measurement accuracy for future assessment of idiopathic scoliosis by photogrammetry. Level of Evidence III; Diagnostic Studies - Investigation of a Diagnostic Test.